Structural and chemical evolution in layered oxide cathodes of lithium-ion batteries revealed by synchrotron techniques. Issue 2 (17th August 2021) - Qian, Guannan; Wang, Junyang; Li, Hong; Ma, Zi-Feng; Pianetta, Piero; Li, Linsen; Yu, Xiqian; Liu, Yijin
Abstract: Rechargeable battery technologies have revolutionized electronics, transportation and grid energy storage. Many materials are being researched for battery applications, with layered transition metal oxides (LTMO) the dominating cathode candidate with remarkable electrochemical performance. Yet, daunting challenges persist in the quest for further battery developments targeting lower cost, longer lifespan, improved energy density and enhanced safety. This is, in part, because of the intrinsic complexity of real-world batteries, featuring sophisticated interplay among microstructural, compositional and chemical heterogeneities, which has motivated tremendous research efforts using state-of-the-art analytical techniques. In this research field, synchrotron techniques have been identified as a suite of effective methods for advanced battery characterization in a non-destructive manner with sensitivities to the lattice, electronic and morphological structures. This article provides a holistic overview of cutting-edge developments in synchrotron-based research on LTMO battery cathode materials. We discuss the complexity and evolution of LTMO's material properties upon battery operation and review recent synchrotron-based research works that address the frontier challenges and provide novel insights in this field. Finally, we formulate a perspective on future directions of synchrotron-based battery research, involving next-generation X-ray facilities and advanced computational developments. Abstract : This article reviews novel synchrotron techniques for studying the structural, chemical, morphological and dynamic complexities in state-of-the-art industry-relevant lithium-ion battery cathode materials.